Influence of elongation and desaturation on chemosensory properties in acrylates and their corresponding 1-alken-3-ones - Bauer, Patrick; Ortner, Eva; Büttner, Andrea (Analytical and Bioanalytical Chemistry, 2022)
Acrylates as well as 1-alken-3-ones are both known to be odour active substances but are generally identified in different materials. Nonetheless, butyl acrylate and 1-octen-3-one were both found to elicit a similar mushroom-like odour in previous studies. This led to the question of whether acrylates and enones with the same overall chain length generally elicited similar odours and whether they had similar odour thresholds. Overall, most of the investigated substances showed a mushroom-like, geranium-like or fruity odour. In contrast, short chained substances elicited garlic-like, lighter gas-like or glue-like, odour qualities, suggesting a correlation between the odour quality and the overall chain length. The results showed that only between the analogue structures butyl acrylate and 1-octen-3-one as well as hexyl acrylate and 1-decen-3-one could similar odour qualities be observed. All investigated substances showed low odour threshold values in air between 0.0032 ng/l(air) (1-hexen-3-one) and 55 ng/l(air) (1-dodecen-3-one). Overall, 1-alken-3-ones revealed a higher dependency on the chain length when compared to their respective acrylates. The introduction of a second terminal double bond led to a decrease of OT values in case of the acrylates and to an increase in case of the ketones that neither contained a second terminal double bond nor a double bond located close to the carbonyl group. Despite their structural similarities, the results suggest that both substance classes are perceived in a different manner and are therefore likely to be recognized by different types of receptors or are related to different activation patterns in multi-receptor stimulation processes.
CRIS-Team WoS Importer:2022-09-30